Comprehensive factorization and universal I-central extensions in the Mal'cev context - Bourn, Dominique (2010)
We show that, under suitable left exact conditions on a re ection functor I, the construction of the associated universal I-central extension is reduced to the comprehensive factorization of a speci c internal functor. This observation produces some existence conditions which hold in particular for any re ection from a Mal'cev variety to any Birkho subvariety